The church in the world : a historical-ecclesiological study of the Church of Uganda with particular reference to post-independence Uganda, 1962-1992 - Niringiye, David Zac (Carlisle, Cumbria, UK, Langham Monographs, 2016)
Niringiye examines several formative periods for the Church of Uganda during concurrent chronological political eras characterized by varying degrees of socio-political turbulence, highlighting how the social context impacted the churchs self-expression. This is an excellent reflection on the Ugandan church bringing global attention to topics that hold great value to society, the church, and the academic community.
Keywords: Church History; Church of Uganda.-- History; Uganda History 1962-1992; Uganda Church History